Menelisik masa depan kakao berkelanjutan: menjembatani kesenjangan kesediaan membayar konsumen di Indonesia: Exploring sustainable cocoa futures: bridging the consumer willingness-to-pay gap in Indonesia - Yuda, Wednes Aria; Guritno, Adi Djoko; Suyantohadi, Atris (Analisis Kebijakan Pertanian, 2025)
The sustainability of cocoa agribusiness in Indonesia is hindered by consumers' unwillingness to pay more for sustainable chocolate products. Willingness to Pay (WTP) becomes important because it determines the extent to which the local market is willing to support sustainability connected to cocoa farmers' welfare upstream and premium cocoa quality. This research objective was to reveal the factors causing such reluctance and its implications for agricultural policy. The data was collected through a survey of 340 consumers and analysed using a logistic regression model. Results of this study reveal that environmental awareness, perceived benefits, and price significantly influence the main determinants of WTP, with an average of IDR 11,228 and a median of IDR 12,500. The younger generation (ages 18−24) shows the highest WTP at IDR 12,114, primarily due to the influence of social media promotions. The main factors determining WTP are environmental awareness, perception of social benefits to farmers, and price sensitivity. These findings affirm the existence of an Attitude Behavior Gap, in which awareness does not always manifest in purchasing behavior. Based on these results, it is recommended to implement an integrated policy comprising digital campaigns to increase awareness, subsidize farmers for sustainable cocoa production, and adopt a blockchain-based certification to create transparent document supply chains to address consumer trust issues regarding sustainability claims.
Keywords: attitude–behavior gap; consumer behavior; environmental awareness; sustainable cocoa; willingness to pay; kakao berkelanjutan; kesadaran lingkungan; kesediaan membayar; perilaku konsumen